Deep chlorophyll a maxima (DCMs) in pelagic Antarctic waters. II. Relation to bathymetric features and dissolved iron concentrations - Holm-Hansen, O.; Kahru, M.; Hewes, Christopher D. (Marine Ecology Progress Series, 2005)
A deep chlorophyll a maximum (DCM) at depths between 60 and 90 m in waters south of the Antarctic Polar Front (APF) occurs only in pelagic waters where the chlorophyll a concentrations in the upper mixed layer (UML) are very low (generally <0.2 mg m–³). Dissolved Fe concentrations in these waters with DCMs are also very low (generally <0.2 nM) and are probably a limiting factor for phytoplankton growth and biomass. DCMs occur in the upper portion of the temperature minimum layer (TML), which is the winter residue of the Antarctic Surface Water (AASW). The higher phytoplankton biomass at these depths is thought to result from higher Fe concentrations in the winter remnant of the AASW as compared to that found in the overlying UML. A survey of the literature indicates that DCMs are located predominately over the deep ocean basins where enrichment of surface waters with Fe from either coastal sediments or from upwelling processes would be minimal. DCMs are not found in coastal waters or in pelagic regions where complex bottom topography causes upwelling of deep water with sufficiently high Fe concentrations to enhance surface chlorophyll a concentrations. Such enrichment of surface waters overlying or downstream of topographical seamounts or ridges that rise to within a few thousand meters of the surface usually results in elevated phytoplankton biomass in the UML and no DCM due to decreased solar irradiance in the TML. The effect of such enrichment of Fe in surface pelagic waters that results from upwelling processes is most pronounced in the Scotia Sea, in the Polar Frontal region downstream of South Georgia, over the Southwest Indian Ridge, over the Kerguelen Plateau, and over the Pacific Antarctic and Southeast Indian Ridges. Published version